PENGARUH KUALITAS LAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN FAMILY DENTAL CLINIC CABANG JATIWARINGIN - Dewi Refiyanti (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
The purpose of this study was to determine the effect of service quality, price and promotion on customer satisfaction at the Jatiwaringin Branch of Family Dental Clinic. This research is included in the category of causal associative research using a quantitative approach. The population in this study were customers of the Jatiwaringin Family Dental Clinic branch for one month, namely 250 customers. The sampling technique used in this study is a probability sampling technique. By using the Slovin formula obtained a sample of 70 respondents. The method of analysis used is simultaneously regression. The conclusion simultaneously service quality, price and promotion can contribute to customer satisfaction. it means that the better the quality of service, price and promotions provided, the customers will be satisfied to do dental care at the Jatiwaringin branch of Family Dental Clinic.